Cover Image, Volume 93, Number 9, September 2021. Issue 9 (16th July 2021) - Barua, Subarna; Hoque, Monirul; Kelly, Patrick J.; Bai, Jianfa; Hanzlicek, Gregg; Noll, Lance; Walz, Heather; Johnson, Calvin; Kyriakis, Constantinos; Wang, Chengming
Abstract : Front Cover Caption : The cover image is based on the Research Article High‐resolution melting curve FRET-PCR rapidly identifies SARS‐CoV‐2 mutations by Subarna Barua et al., https://doi.org/10.1002/jmv.27139 .